Wastewater-irrigated vegetables: Market handling versus irrigation water quality - Ensink, Jeroen H.J.; Mahmood, Tariq; Dalsgaard, A. (2007)
Objective and methods: Vegetables irrigated with untreated domestic wastewater were, at the time of harvest, analysed for the presence of the faecal indicator, Escherichia coli, and helminth eggs in Faisalabad, Pakistan. Vegetables from the same harvested batch were collected approximately 12 h later from the local market. Results: The survey found relatively low concentrations of E. coli (1.9 E. coli per gram), but relatively high concentrations of helminths (0.7 eggs per gram) on vegetables collected from agricultural fields. Higher concentration of both E. coli (14.3 E. coli per gram) and helminths (2.1 eggs per gram) were recovered from the vegetables collected from the market. Conclusions: The results of the survey suggest that unhygienic post harvest handling was the major source of produce contamination. Interventions at the market, such as the provision of clean water to wash produce in, are better ways to protect public health and more cost effective than wastewater treatment.